1992
DOI: 10.1063/1.106891
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence decay in disordered low-dimensional semiconductors

Abstract: The luminescence decay of excitons in disordered low-dimensional semiconductors with quantum confinement is shown experimentally to be characterized by a nonexponential profile and an absence of spectral diffusion. We are able to describe this luminescence as a hopping-assisted recombination using the correlation function approach to nondispersive transport developed by H. Scher, M. F. Shlesinger, and J. T. Bendler [Phys. Today 41, 26 (1991)]. We suggest a simple derivation of analytical functions which accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(58 citation statements)
references
References 10 publications
4
53
1
Order By: Relevance
“…Chen et al [9] studied the decay of luminescence in porous silicon and in CdSe-ZnSe superlattice, and found that the stretched-exponential behavior…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [9] studied the decay of luminescence in porous silicon and in CdSe-ZnSe superlattice, and found that the stretched-exponential behavior…”
Section: Introductionmentioning
confidence: 99%
“…The difference in coefficients D and D* can be related to the presence of a quadrupole (or higher moments of) interaction of excitons or an exchange interaction in the case of a substantial overlapping of their wavefunctions. Obtained ordinary differential equation (21) N excitation level, which was repeatedly noted by many researchers (see, e.g., (Chen et al, 1992) N initial excitation level. As will be shown in the next section, such a calculation can be performed in terms of the proposed model.…”
Section: Kinetic Equations For the Relaxation Processes In Nc-si Ensementioning
confidence: 99%
“…Numerous attempts were made to explain the causes of the stretched exponent of PL relaxation in the systems given above. For example, the authors of (Chen et al, 1992;Kanemitsu, 1996) relate this character of luminescence drop to the presence of disordered regions in these objects, which can be caused by a shape distribution of nanocrystals or a variation in their spatial arrangement. These factors induce a scatter of the recombination energies and probabilities of electronhole pairs, which is likely to result in luminescence kinetics of type (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations